Махгалын "Уран заллага"-ын эгшиг тэмдэглэгээнд хийсэн шинжлэл - П., Даваапил (Mongolian Studies, 2023)
The rituals of wrathful deities, such as Ten Dharmapalas and praises of ten-direction and three- hour deities, such as Buddha Shakyamuni are recited from the third spread of Buddhism. In addition, their melodies were noted with special signs and symbols. Researches and surveys on the Buddhist melody-reciting are not much. Especially, there are few researches focusing to melodies in connection to its composition and notation. So, I tried in this article to study the melodies of Mahgal’s "Urin Zallaga" with regard to its composition and notation. I chose some parts of scriptures of the wrathful deities of "Shankhin Baruun Khuree Monastery", "Gandan Tegchenling Monastery", "Lama Gegeen Monastery" and "Zuun Khuree Dashchoilin Monastery" as the main sources.